Bacteriological Etiology of Empyema Thoracis Patients Admitted in A Tertiary Care Hospital (Bangladesh Journal of Medicine, 2024)
Background: Empyema thoracis is the most common complication of pneumonia and is associated with severe morbidity and mortality. Management of empyema thoracis is complex and needs a multimodal approach. Antibiotic therapy is very crucial in management of empyema thoracis and to ensure appropriate antibiotic therapy, epidemiological data is essential. This study aimed to explore the bacteriological profile of empyema thoracis in a tertiary care hospital. Methods: This cross-sectional study was carried on 30 patients admitted in the Department of Medicine and Department of Respiratory Medicine, Sir Salimullah Medical College and Mitford Hospital, Dhaka over a period of six months.Results: Mean age of the patients was 38±10.94(SD) years of age with a male predominance (66.7% male and 33.3% female). Presenting symptoms were cough (86.7%), fever (83.3%), expectoration (76.7%), chest pain (70.0%), loss of appetite (50.0%), malaise (46.7%) and hemoptysis (10.0%). The major etiology was the thoracic empyema (56.7%) followed by pneumonia (16.67%), lung abscess (10.0%), liver abscess (6.7%), lung cancer (3.3%), secondary infection (3.3%) and undetermined cases responding to antibiotics (3.3%). Bacteriological profile showed Mycobacterium tuberculosis (56.7%), S. aureus (6.7%), S. pyogen (6.7%) , E. coli (3.3%), Klebsiella (3.3%) and Pseudomonas (6.7%). Conclusion: It was concluded from the study, more than half of empyema thoracis was eitiologically tubercular. Bangladesh J Medicine 2024; 35: 187-194